2018
DOI: 10.14716/ijtech.v9i3.279
|View full text |Cite
|
Sign up to set email alerts
|

Exploration of Various Indonesian Indigenous Plants as Natural Coagulants for Synthetic Turbid Water

Abstract: The availability of clean water is one of the biggest global problems, especially in developing countries. The simplest way to treat turbid water is by using coagulation. However, the utilization of chemical coagulants such as alum and ferrum has several drawbacks, including a high sludge volume and negative health impact when the water is consumed. Natural coagulants offer a better option, especially because of their availability, low price, lower sludge volume, and effectiveness comparable with chemical coag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 14 publications
(3 citation statements)
references
References 23 publications
(30 reference statements)
0
3
0
Order By: Relevance
“…To the best of authors' knowledge, this study is the first study that reported utilization of adsorbed protein on citrate modified Fe 3 O 4 as magnetic coagulant. Based on our previous study, leucaena protein could act as natural coagulant to remove turbidity [30] and color [31]. The Fe 3 O 4 was modified using citrate ion that acted as a bridge for protein adsorption.…”
Section: Introductionmentioning
confidence: 99%
“…To the best of authors' knowledge, this study is the first study that reported utilization of adsorbed protein on citrate modified Fe 3 O 4 as magnetic coagulant. Based on our previous study, leucaena protein could act as natural coagulant to remove turbidity [30] and color [31]. The Fe 3 O 4 was modified using citrate ion that acted as a bridge for protein adsorption.…”
Section: Introductionmentioning
confidence: 99%
“…Studies have been performed previously on the application of leucaena seed powder to treat synthetic turbid water. Kristianto et al (2018) reported that the leucaena seed powder gave comparable performance to Moringa oleifera when it was used to remove water turbidity (Kristianto et al 2018). Another study by Al-Mamun and Basir (2016) showed that a maximum of 76% turbidity removal has been achieved when using leucaena NaCl seed's extract (Al-Mamun and Basir 2016).…”
Section: Introductionmentioning
confidence: 99%
“…To the best of authors' knowledge, this study is the rst study that reported utilization of adsorbed protein on citrate modi ed Fe 3 O 4 as magnetic coagulant. Based on our previous study, leucaena protein could act as natural coagulant to remove turbidity [30] and color [31]. The Fe 3 O 4 was modi ed using citrate ion that acted as a bridge for protein adsorption.…”
Section: Introductionmentioning
confidence: 99%